Selection an airsoft rifle for urban combat using the hybrid multi-criteria decision-making model BORDA-AHP-SAW and Entropy-Critic-FanMa-SAW - Aleksic, Aleksandar; Zivkovic, Misa; Projovic, Damir; Petronijevic, Milorad; Bozanic, Darko (Vojnotehnički glasnik / Military Technical Courier, 2025)
Тhe paper presents the method of applying multi-criteria decision-making methods in order to select an airsoft replica of an automatic rifle for practicing tactical actions in urban combat. First, the criteria were ranked by experts according to which the alternative would be selected. By applying the BORDA and AHP methods, the weighting coefficients of the criteria were determined, and then the most favorable alternative was selected by applying the SAW method. The selection procedure was repeated when the selection was made without experts, but the weighting coefficients of the criteria were determined by the objective methods Entropy-Critic-FanMa and a comparative analysis of the results was performed. The aim of the paper is to select the most effective airsoft rifle for professional and civilian use for practicing tactical actions and actions in urban combat by combining multi-criteria decision-making methods. Minimal resource consumption is always the starting point today, while ensuring the most efficient way to practice tactical actions that are realistic to real conditions.For the first time, the method of determining the weighting coefficients of criteria using multidisciplinary methods of multi-criteria decision-making on a specific problem in the field of Tactics with weapons systems was shown with expert opinion, and then the results were compared if experts were not engaged. Experts in the field of tactics and weapons from the Military Academy first selected and ranked seven criteria. Then, their opinions were sublimated using the BORDA method, and the results were entered into the AHP method to select the weighting coefficients of the criteria. Finally, the most favorable alternative was selected based on the SAW method. Since the above procedure for determining the weighting coefficients of the criteria was calculated for the first time by engaging experts in this way, the procedure for selecting the most favorable alternative was repeated, without engaging experts, but the weights of the criteria were determined using objective methods and the results were compared through comparative analysis. The alternatives are five airsoft rifles with a hopup chamber, some of which are used at the Military Academy and in special army units for training in various combat-tactical actions, and in civilian life they are used by airsoft weapon enthusiasts.Choosing the most affordable airsoft rifle, which will provide minimal resource consumption and maximum performance and the greatest possible realism to the combat situation when practicing tactical actions in an urban environment.The solution, with a comparative analysis of the results obtained in two ways, takes into account the simultaneous optimization of seven criteria, which differ slightly, in order to select the most effective airsoft rifle for practicing tactical procedures in order to provide conditions that are closest to a real combat situation at short distances.
Keywords: airsoft rifle, selection, BORDA, AHP, SAW, Entropy, Critic, FanMa method